Evaluasi Manajemen Logistik Obat di Instalasi Farmasi Rumah Sakit Umum Daerah Kabupaten Sorong - Dwi Andriani; Cecep Darmawan; Rinawati Rinawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Drug logistics management is a crucial element in the hospital pharmaceutical service system because it directly impacts the availability, quality, and efficiency of drug use. Effective logistics management will support the achievement of optimal health services and ensure patients receive the drugs they need. This study aims to evaluate drug logistics management in the Pharmacy Installation of Sorong Regency Hospital, by examining the entire logistics cycle, from selection, planning, procurement, receipt, storage, distribution, destruction and withdrawal, control, administration of recording and reporting, to drug availability. The research method used is descriptive with qualitative methods aimed at obtaining more in-depth information about drug logistics management in the Pharmacy Installation of Sorong Regency Hospital. The results of this study indicate that the implementation of drug logistics management in hospitals has adhered to the provisions of the Minister of Health Regulation No. 72 of 2016 concerning Pharmaceutical Service Standards in Hospitals. However, in practice, various obstacles remain, such as limited funding, drug shortages at distributors, and obstacles in drug delivery which resulted in the stock shortage of several drugs in the pharmacy installation so that patients were forced to buy drugs outside the hospital. This study is expected to contribute to strengthening hospital policies in drug logistics management systems and serve as a reference for further research.